Comparative analysis of the burnout syndrome index between contract and freelance physiotherapists: An observational study. - Grande-Alonso, Mónica; Castillo-Alcañiz, Beatriz; Paraíso-Iglesias, Pablo; Cuenca-Martínez, Ferran; La Touche, Roy; Vidal-Quevedo, Celia (Work, 2023)
BACKGROUND: Burnout syndrome has been extensively studied in different health science professions. It has been less studied in physiotherapy than in professions such as medicine. Moreover, it is not known how the working condition influences this syndrome. OBJECTIVE: The main objective of this study was to compare the burnout index between contract and freelance physiotherapists in the private sector in the Community of Madrid, Spain. METHODS: A cross-sectional study was performed with 174 participants divided into 2 groups; one group was composed of contract physiotherapists (n = 87) and the other group was composed of freelance physiotherapists (n = 87). A Mann–Whitney U test was performed for comparison between the groups. Spearman's correlation coefficient was used to analyze the correlations between the burnout syndrome index and the secondary variables. RESULTS: There were statistically significant differences when comparing the groups, with a large effect size for the burnout index with a higher rate among contract physiotherapists (78 [71–84.75]) than in freelance physiotherapists (61.5 [55–72.75]).There were also significant differences in the type of patients treated, number of patients treated per day, time spent per patient, and the annual salary range between the contract and freelance physiotherapists. CONCLUSION: Contract physiotherapists who participated in this study had a significantly higher burnout syndrome index than freelance physiotherapists. Other socio-occupational variables were also found to be related to the burnout syndrome index in freelance physiotherapists and contract physiotherapists. The results of this study could be of interest for new occupational health strategies to reduce the burnout index in contract physiotherapists.